Penguatan Numerasi bagi Guru Sekolah Menengah Kejuruan (SMK) dalam Mendukung Implementasi Kurikulum Merdeka - Diandra Chika Fransisca (LPPM IT Telkom Purwokerto, 2025)
The Numeracy Strengthening Workshop program was conducted to enhance the competence of vocational high school teachers in integrating numeracy into project-based learning in line with the Merdeka Curriculum. This activity aimed to improve teachers’ understanding of numeracy concepts, strengthen their skills in designing contextual problems, and develop their ability to interpret statistical and visual data. The implementation employed the Participatory Action Learning (PAL) approach, which consists of four main stages: planning, action, observation, and reflection. Through this approach, participants were actively involved in interactive lectures, group discussions, and hands-on project-based numeracy applications. The results revealed a significant improvement in teachers’ holistic understanding of numeracy, their ability to apply mathematical reasoning and data analysis, and their capacity to design relevant project-based learning activities aligned with real-world contexts. The program also fostered reflective and collaborative attitudes among teachers as part of continuous professional development. Therefore, this community service activity effectively strengthened teachers’ numeracy literacy and supported the successful implementation of the Merdeka Curriculum in vocational education settings.